2005
DOI: 10.1136/jcp.2004.020685
|View full text |Cite
|
Sign up to set email alerts
|

Osseous metaplasia in a tubular adenoma of the colon: Figure 1

Abstract: An 85 year old woman presented with a one month history of change in her bowel habits in the form of alternating diarrhoea and constipation. She also noted some rectal bleeding. Flexible sigmoidoscopy revealed a 1.5 cm polyp 30 cm from the anus. The polyp was removed during the sigmoidoscopy by electrocautery and sent for histological examination. The polyp was a tubular adenoma with mild dysplasia. The adenoma contained numerous foci of metaplastic bone. These consisted of irregular islands of mineralised ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
0
20
0
3
Order By: Relevance
“…In time, studies will determine if the expression of pluripotency proteins can be found in vivo (as seen in vitro) and if their function underlies this plasticity phenotype. Encouragingly, rare events have been described by pathologists (choristomas, heterotopias, metaplasias, or ectopic tissues) that consist of normal tissues in abnormal locations, such as bone in the colon and eye (30,31), liver in gallbladder (32) and pancreas in brain (33). Thus, cells with extensive lineage plasticity exist in healthy tissues and evidence for their plasticity is sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
“…In time, studies will determine if the expression of pluripotency proteins can be found in vivo (as seen in vitro) and if their function underlies this plasticity phenotype. Encouragingly, rare events have been described by pathologists (choristomas, heterotopias, metaplasias, or ectopic tissues) that consist of normal tissues in abnormal locations, such as bone in the colon and eye (30,31), liver in gallbladder (32) and pancreas in brain (33). Thus, cells with extensive lineage plasticity exist in healthy tissues and evidence for their plasticity is sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, heterotopic bone formation is often associated with inflammation and/or ulceration, or with the presence of mucin production and extravasation. Repeated local trauma, factors released from adenoma cells or peculiar characteristics of the rectal mucosa were also considered as possible factors in the pathogenesis [25,26] . In our case, mucin lakes and inflammatory infiltrates were both in close proximity to the osse- ous foci.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, seven lesions were neoplastic (four tubular adenomas, and three tubulovillous adenomas), while 15 lesions were non-neoplastic (seven juvenile polyps, six inflammatory polyps, and two serrated adenomas). In two lesions histology finding was not specified [1,[3][4][5][6][7][8]. Our patient had non-neoplastic inflammatory polyp.…”
Section: Discussionmentioning
confidence: 88%